Javanese-Bashu Cultural Art Adaptation - Anjana, Regina Pravangasta Dyang; Husnul, Riotania (Journal of Maobi, 2023)
This article aims to find out and identify the cultural differences that exist in the two regions, as well as being one of the efforts to preserve regional cultural heritage. The writing of this article uses quantitative methods, namely by collecting data found on the internet and related journals. Cultural acculturation between Javanese and Chinese is a process of mutual interaction and influence between the two cultures. Both cultures have a long history with their characteristics. Artistic elements can merge through cultural contact and create new forms of cultural adaptation. Cultural exchange between Javanese and Chinese occurs in various areas of life, such as language, religion, art, and lifestyle. For example, many absorbing words are used from both languages, the use of traditional Chinese clothing in specific festivals, the adoption of Chinese architectural styles in the construction of houses, and the presence of Chinese cuisine flavours, which are in the taste of Javanese cuisine. The acculturation of Javanese and Chinese cultures provides opportunities for both cultures to explore and share experiences. This creates a rich diversity of unique and rich cultural identities. This acculturation is also an important example of how cultures can evolve through interaction and exchange between different cultural groups.